SINTESIS ETIL LAURAT DARI ASAM LAURAT MENGGUNAKAN KATALIS ASAM SULFAT PEKAT - Andi Nursyafinah; Nurhaeni Nurhaeni; Erwin Abdul Rahim (KOVALEN: Jurnal Riset Kimia, 2016)
The aims of these research are to find out the comparison of the ratio of lauric acid molar and ethanol  (m/v), the time of mixing and the best catalyst volume to produce lauric ethyl with the highest degree of esterification by using volumetric method. Synthesize of ethyl lauric from lauric acid with ethanol did by using thick sulphate acid p.a as the catalyst with comparison of lauric acid with ratio 1:3, 1:4, 1:5, 1:6, 1:7. The variation of mixing time are 1, 2, 3, 4, 5 hour. The catalyst variation are 1, 2, 3, 4, and 5 mL. This research used random variable in the confidence interval 95%. The result of this research showed that the best molar lauric acid ratio and ethanol is 1: 7 (m/v) and esterification degree is 59,701 %. The best mixing time is 5 hour, and esterification is 53,283%, While catalyst volume variation is 1 mL with esterification degree 87,611 % Keywords : Lauric Acid, Ethyl Lauric, Esterification Degree, Volumetric Method